Do Managers Disclose or Withhold Bad News? Evidence from Short Interest - Bao, Dichu; Kim, Yongtae; Mian, G. Mujtaba; Su, Lixin (Nancy) (The Accounting Review, 2019)
ABSTRACT Prior studies provide conflicting evidence as to whether managers have a general tendency to disclose or withhold bad news. A key challenge for this literature is that researchers cannot observe the negative private information that managers possess. We tackle this challenge by constructing a proxy for managers' private bad news (residual short interest) and then perform a series of tests to validate this proxy. Using management earnings guidance and 8-K filings as measures of voluntary disclosure, we find a negative relation between bad-news disclosure and residual short interest, suggesting that managers withhold bad news in general. This tendency is tempered when firms are exposed to higher litigation risk, and it is strengthened when managers have greater incentives to support the stock price. Based on a novel approach to identifying the presence of bad news, our study adds to the debate on whether managers tend to withhold or release bad news. Data Availability: Data used in this study are available from public sources identified in the study.